2014
DOI: 10.1370/afm.1662
|View full text |Cite
|
Sign up to set email alerts
|

Practice Environments and Job Satisfaction in Patient-Centered Medical Homes

Abstract: PURPOSE We undertook a study to evaluate the effects of medical home transformation on job satisfaction in the primary care setting. METHODSWe collected primary data from 20 primary care practices participating in medical home pilot projects in Rhode Island and Colorado from 2009 to 2011. We surveyed clinicians and staff about the quality of their practice environments (eg, office chaos, communication, difficulties in providing safe, highquality care) and job satisfaction at baseline and 30 months, and about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…[45] Perceived workload is a more potent predictor of burnout than objective measures of workload, such as case load, because practitioners, like all human beings, are frequently motivated by perceptions rather than objective reality. [46] Strategies such as allowing a healthy degree of control (especially over schedules) plus implementing team-based [47,48] and collaborative care models [49] can reduce perceptions of heavy workload.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Perceived workload is a more potent predictor of burnout than objective measures of workload, such as case load, because practitioners, like all human beings, are frequently motivated by perceptions rather than objective reality. [46] Strategies such as allowing a healthy degree of control (especially over schedules) plus implementing team-based [47,48] and collaborative care models [49] can reduce perceptions of heavy workload.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that changes in the work condition following health system reform can influence HCPs' job satisfaction and work experiences [17][18][19][20]. In fact, adopting new practice models requires changing existing practices and also organisational change which can create undue stress to HCPs [7].…”
Section: Abstract: Job Satisfaction Primary Care Interventions Heamentioning
confidence: 99%
“…To date, studies which address job satisfaction of HCPs in Malaysia remain scarce. The majority of studies evaluating job satisfaction following primary care transformation are mainly conducted in developed countries and often lack of a comparison group [18][19][20]27]. Therefore, the aim of this study is to evaluate the effects of EnPHC interventions implemented at facility level on HCPs' job satisfaction in the LMIC context.…”
Section: Abstract: Job Satisfaction Primary Care Interventions Heamentioning
confidence: 99%
“…9 Yet few have reported how PCMH practice transformation affects satisfaction among community-based physicians. Of those few, researchers reported factors including strains on practice site resources and cultures, 10,11 practice “chaos,” 12 and the adequacy of reimbursements in light of PCMH transformation. 13 …”
mentioning
confidence: 99%